2020
DOI: 10.7150/thno.45848
|View full text |Cite
|
Sign up to set email alerts
|

Tumor progression locus 2 (TPL2) in tumor-promoting Inflammation, Tumorigenesis and Tumor Immunity

Abstract: Over the years, tumor progression locus 2 (TPL2) has been identified as an essential modulator of immune responses that conveys inflammatory signals to downstream effectors, subsequently modulating the generation and function of inflammatory cells. TPL2 is also differentially expressed and activated in several cancers, where it is associated with increased inflammation, malignant transformation, angiogenesis, metastasis, poor prognosis and therapy resistance. However, the relationship between TPL2-driven infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 161 publications
(331 reference statements)
0
23
0
Order By: Relevance
“…Extensive studies have shown that systemic inflammation plays an essential regulatory role in malignant tumors' occurrence and development. [30][31][32] Inflammatory factors, including acute-phase proteins such as C-reactive protein and albumin, may come from the systemic response to malignant tumors or from the secretion of malignant cells. 33 The interaction between host and tumor cells may lead to tumor progression or retraction.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have shown that systemic inflammation plays an essential regulatory role in malignant tumors' occurrence and development. [30][31][32] Inflammatory factors, including acute-phase proteins such as C-reactive protein and albumin, may come from the systemic response to malignant tumors or from the secretion of malignant cells. 33 The interaction between host and tumor cells may lead to tumor progression or retraction.…”
Section: Discussionmentioning
confidence: 99%
“…What is the theme of this study, however, is that care has to be taken in touching on the relationships between MAP3K8 and human cancers. Although MAP3K8 was originally recognized as an oncogene since its discovery in 1991, genetic sequence analyses identi ed rare MAP3K8 mutations which is much less than altered expression and abnormal activation in human cancers [6]. Previous studies have found that overexpression and increased activation of MAP3K8 are main events associated with increased tumorigenesis including initiation, promotion and progression as well as poor prognosis [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…Although MAP3K8 was originally recognized as an oncogene since its discovery in 1991, genetic sequence analyses identi ed rare MAP3K8 mutations which is much less than altered expression and abnormal activation in human cancers [6]. Previous studies have found that overexpression and increased activation of MAP3K8 are main events associated with increased tumorigenesis including initiation, promotion and progression as well as poor prognosis [6,23]. In addition, reduced MAP3K8 expression is also related to poor prognosis and tumor aggressiveness in some cancers such as non-small cell lung cancer (NSCLC) [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have shown that systemic in ammation plays an essential regulatory role in malignant tumors' occurrence and development [24][25][26]. In ammatory factors, including acute-phase proteins such as C-reactive protein and albumin, may come from the systemic response to malignant tumors or from the secretion of malignant cells [27].…”
Section: Discussionmentioning
confidence: 99%